Transcriptome analysis provides insight into the regulatory mechanisms underlying pollen germination recovery at normal high ambient temperature in wild banana (Musa itinerans) - Zhang, Chunyu; Zhang, Chengyu; Xu, Xiaoqiong; Liao, Minzhang; Tong, Ning; Zhang, Zihao; Chen, Yukun; Xu Han, Xu; Lin, Yuling; Lai, Zhongxiong (Frontiers in Plant Science, 2023)
In the current analysis, we examined the changes in viability of wild banana pollens at different temperatures by in vitro germination, and found that the germination ability of wild banana pollens cultured at 28°C for 2 days was higher than that of pollens cultured at 23°C (pollens that could not germinate normally under low temperature stress), 24°C (cultured at a constant temperature for 2 days) and 32°C (cultured at a constant temperature for 2 days). To elucidate the molecular mechanisms underlying the germination restoration process in wild banana pollens, we selected the wild banana pollens that had lost its germination ability under low temperature stress (23°C) as the control group (CK) and the wild banana pollens that had recovered its germination ability under constant temperature incubation of 28℃ for 2 days as the treatment group (T) for transcriptome sequencing. A total of 921 differentially expressed genes (DEGs) were detected in CK vs T, of which 265 were up-regulated and 656 were down-regulated. The combined analysis of Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) revealed that the activation, metabolism of various substances (lipids, sugars, amino acids) play a major role in restoring pollen germination capacity. TCA cycle and the sesquiterpenoid and triterpenoid biosynthetic pathways were also significantly enriched in the KEGG pathway. And we found that some DEGs may be associated with pollen wall formation, DNA methylation and DNA repair. The cysteine content, free fatty acid (FFA) content, H2O2 content, fructose content, and sucrose content of pollen were increased at treatment of 28℃ , while D-Golactose content was decreased. Finally, the GO pathway was enriched for a total of 24 DEGs related to pollen germination, of which 16 DEGs received targeted regulation by 14 MYBs. Our study suggests that the balance between various metabolic processes, pollen wall remodelling, DNA methylation, DNA repairs and regulation of MYBs are essential for germination of wild banana pollens.